Subhyaloid Hemorrhage after Bungee Jumping Experience. A Case Report - Stráňava, J; Ugarova, D; Stepanov, A (Ceska a slovenska oftalmologie, 2025)
Subhyaloid hemorrhage is defined as bleeding between the internal limiting membrane (ILM) and the posterior hyaloid membrane. The condition typically manifests itself in acute visual impairment. Causes include the Valsalva maneuver, Terson's syndrome, age-related macular degeneration (ARMD), trauma, hypercoagulable and hyperviscosity states, uncontrolled blood pressure, diabetes mellitus and leukemia. Prolonged presence of blood in the macular region can lead to the development of an epiretinal membrane and toxic damage to the retinal pigment epithelium and photoreceptors due to iron ions. In this case report we present a 32-year-old patient who was treated at the ophthalmology outpatient clinic of the Regional Hospital in Mladá Boleslav for subhyaloid hemorrhage in the right eye following a bungee jumping experience. The patient was successfully treated with Nd -YAG hyaloidotomy, which resulted in a good therapeutic outcome and full restoration of visual acuity.
Keywords: dospělí; retinální krvácení; Adult; Nd-YAG laser; lidé; Retinal Hemorrhage; Hyaloidotomy; Humans; Male; Subhyaloid hemorrhage; mužské pohlaví